PENGARUH DISIPLIN KERJA DAN FASILITAS KERJA TERHADAP EFEKTIFITAS PELAYANAN TEHNIK DI PT. PLN RAYON METRO - LAMPUNG - Ariani, Nora (Katalogis, 2018)
This research was a mixed-method (quantitative and qualitative). The data were collected through questionnaires as the main instrument and documentation and interviews as supporting instruments. The research population was all technical service employees, technical supervisors, and customers who complain at PT. PLN Rayon Metro. The sample totaled 40 respondents using the cluster sampling method; the sample was based on a predetermined population (selected sample) which consisted of 20 employees and 20 customers. The results of the research show that; (1) There is an influence of work discipline on the effectiveness of technical services; (2) There is an influence of work facilities on the effectiveness of technical services; (3) There is an influence of work discipline and work facilities on the effectiveness of technical services. To increase the effectiveness of technical services, it is hoped that employees and PT. PLN can create a conducive work environment, by continuing to improve self-discipline, and also the company should provide good facilities and according to standards both in terms of quantity and safety. Further, it is also necessary to have good cooperation between units and regions in the work environment of PT. PLN.